The Influence of Product Placement in Korean Drama on Consumer Purchase Intentions - Nurfarhanah Umairah Binti Amirrulhisam; Wan Nur Fazni Wan Mohamad Nazarie; Norailis Ab Wahab (AID Academy, 2024)
Product placement is an effective marketing communication tool. Still, it faces challenges such as unpredictable buyer numbers, minimal impact on sales, and lack of control over the product's portrayal in films. Addressing these issues is crucial to prevent misrepresentation and ensure a positive return on investment in marketing. This research aims to analyze the influence of product placement as a marketing strategy in Korean dramas. Specifically, the study evaluates the effectiveness of product placement by examining several factors: the perceived influence of actors, the congruence between the product and the storyline, the perceived influence of the product's function, brand recall, and brand recognition. The objective is to assess how these factors contribute to the success of product placement amidst uncertainties in marketing strategies in Malaysia. The methodology involves a questionnaire survey with 300 respondents using a non-random sampling method. This study is supported in the Parasocial Interaction theory, which explores the interaction between consumers and media personas and its influence on consumer behavior. Data analysis is conducted using SPSS, such as factor analysis, reliability tests, normality tests, and multiple regression to evaluate the impact of various factors on the effectiveness of product placement. The findings reveal that the effectiveness of product placement in Korean dramas is significantly influenced by storyline and product function, which have a substantial relationship with Malaysian consumers' purchase intentions. Conversely, the perceived influence of actors, brand recall, and brand recognition did not significantly impact purchase intentions. These results suggest the need for further refinement and improvement in these areas to enhance the overall effectiveness of product placement in Korean dramas on consumer purchase intentions.